2021
DOI: 10.3390/foods10051119
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis Combined with Multivariate Statistical Methods to Determine the Geographical Origin of Milk from Four Regions in China

Abstract: Traceability of milk origin in China is conducive to the implementation of the protection of regional products. In order to distinguish milk from different geographical distances in China, we traced the milk of eight farms in four neighboring provinces of China (Inner Mongolia autonomous region, Hebei, Ningxia Hui autonomous and Shaanxi), and multivariate data analysis was applied to the data including elemental analysis, stable isotope analysis and fatty acid analysis. In addition, orthogonal partial least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Multivariate data analysis, such as principal component analysis (PCA) and hierarchical cluster analysis (HCA), is used to process a large amount of data, assisting in the interpretation of the results [21]. In food analysis, these techniques are often used in classifcation, determination of the geographic origin, and evaluation of the viability of samples according to their chemical properties [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate data analysis, such as principal component analysis (PCA) and hierarchical cluster analysis (HCA), is used to process a large amount of data, assisting in the interpretation of the results [21]. In food analysis, these techniques are often used in classifcation, determination of the geographic origin, and evaluation of the viability of samples according to their chemical properties [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Further, another feasibility study conducted in New Zealand has shown that the δ 13 C and δ 15 N isotopes of milk casein reflect the inherent geo-climatic variation across dairy farms sampled in the south and north islands [17]. Several studies conducted with milk samples collected from various provinces in China have successfully shown the ability of stable isotopes to verify the geographic origin [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In order to protect the PGI products, researchers have put forward a fingerprint tracing method, that is, using chemical parameters to build the fingerprint of geographical indication products [ 4 ] and comparing it with the fingerprint of the testing sample to determine whether the testing sample is the geographical indication product. At present, the chemical parameters used in the traceability of animal-origin food include stable isotopes [ 5 ], mineral elements [ 6 ], fatty acid content [ 7 , 8 ], amino acid content [ 9 ], and metabolites [ 10 ]. Stable isotopes are commonly used to characterize geographical origin information and to describe agricultural products’ origin information, where δ 2 H and δ 18 O can be used to distinguish altitude, δ 15 N can be used to determine the type of grazing vegetation, and δ 13 C can determine the type of animal feed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%